2010
DOI: 10.1093/jb/mvq139
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid mutation at position 170 of human parainfluenza virus type 1 fusion glycoprotein induces obvious syncytium formation and caspase-3-dependent cell death

Abstract: An escape mutant of human parainfluenza virus type 1 (hPIV1), which was selected by serial passage in the presence of a sialidase inhibitor, 4-O-thiocarbamoylmethyl-2-deoxy-2,3-didehydro-N-acetylneur-aminic acid (TCM-Neu5Ac2en), exhibited remarkable syncytium formation and virus-induced cell death in LLC-MK2 cells but no difference in susceptibility for the sialidase inhibitor TCM-Neu5Ac2en from that of wild-type hPIV1 strain C35 (WT). The mutant virus also had higher replication and plaque formation abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Literature data showed that substitution of one amino acid in HPIV1 proteins could significantly influence their biological features (Bartlett et al, 2007;Bousse et al, 1995Bousse et al, , 2006Takaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Literature data showed that substitution of one amino acid in HPIV1 proteins could significantly influence their biological features (Bartlett et al, 2007;Bousse et al, 1995Bousse et al, , 2006Takaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For detection of IFV‐induced cell death, DNA fragmentation in cells derived from BALF was analyzed by flow cytometry . In brief, cells in BALF were collected by centrifugation (200 g , 9 min, 4°C) and fixed with 70% ethanol for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…6,7) The F glycoprotein is a common spike protein in paramyxovirus and mediates both membrane fusion between the virus and cell (virus-cell fusion) and membrane fusion between cells (cell-cell fusion). 8) Nascent HN and F glycoproteins are abundantly expressed on the cell surface membrane of paramyxovirus-infected cells. The F glycoprotein on the cell surface membrane induces cell-cell membrane fusion between virus-infected cells and their neighboring non-infected cells, resulting in multinucleated giant cell formation, called syncytium formation.…”
Section: Introductionmentioning
confidence: 99%
“…9) Syncytium formation has been reported to be associated with paramyxovirus growth. 8,10) Remarkable syncytium formation can be seen in cells infected with some paramyxoviruses such as Sendai virus (SeV), respiratory syncytial virus, and human parainfluenza virus type 3 (hPIV3). 11,12) hPIV1 shows little syncytium formation during virus growth in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation